The impact of witnessing athletic injury: A qualitative examination of vicarious trauma in artistic gymnastics - Day, M. C.; Schubert, N. (Journal of Sports Sciences, 2012)
We explored how athletes respond and cope after witnessing athletic injury in others participating in the same sport. Participants were eight competitive female artistic gymnasts aged 21-25 years. In the previous 3 years, participants had witnessed a serious athletic injury of another gymnast that had required hospital treatment. Participants took part in semi-structured interviews in which they were asked to discuss their experiences of witnessing injury, including descriptions of the injury's occurrence. Data were analysed using hierarchical content analysis. Following acute reactions to witnessing injury, participants reported experiencing intrusive cognitions and engaged in avoidance coping strategies. Participants reported gradually engaging in more approach coping strategies which served to lower their perceptions of vulnerability to injury. Despite the complex nature of trauma, suggestions may be made to assist applied sport psychologists working with athletes who have witnessed athletic injury.